Studi Perbandingan Penggunaan Software Tekla dan Konvensional dalam Perhitungan Bar Bending Schedule pada Proyek Kantor Inkasa Kertajaya - Prasetia, Mohamad Adi; Rochmah, Nurul; Triana, Masca Indra (Politeknik Negeri Lhokseumawe, 2024)
In the construction sector, there is the term BIM, which stands for Building Information Modeling. BIM is a system that forms a process in conveying information or digital references for more accurate physical and functional characteristics about a construction which includes AEC (Architecture, Engineering, and Construction). BIM includes sharing information related to a project/building, from the beginning of planning (pre-construction), implementation (construction), maintenance (maintenance) to demolition (demolition) of the building. The dimensional approach to BIM is known to have advantages, in contrast to conventional applications which are generally still limited to the 3D stage. It is known that BIM can be utilized up to the concepts of 4D (scheduling), 5D (estimating), 6D (sustainability), and 7D (facility management applications) approaches.In this final assignment proposal, we will discuss the use of the Building Information Modeling (BIM) concept by creating 3D modeling of structural work using Tekla Student Version software in working on bar bending schedules. Tekla software can produce iron calculations on beams and columns assisted by Microsoft Excel software. The calculation results from Tekla will be compared with conventional methods, comparisons will also be made regarding processing time, calculations, cost estimates and material waste in beam column reinforcing steel.It is hoped that this can provide an illustration that using computer software is more effective, efficient and can minimize material waste. So research is needed in implementing the BIM concept to see the differences in results between software and (conventional) project data. The building used as the research object is the Inkasa Office Project Construction, Kertajaya Office which is located in the city of Surabaya, East Java, has 5 floors + 1 roof, a land area of 33m long, 27m wide and a building area of 468m2. The function of the building is as an office.